Development of Predictive Current Controller for Multi-Port DC/DC Converter - Santhosh T K; Govindaraju C (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
This paper investigates the utilization of a predictive current control for a fourport DC/DC power electronic converter with an input port, two storage portsand a load port suitable for a Hybrid Electric Vehicle. Being a power converterwith multiple ports, it has different operating modes. While the Stateflow con-troller is employed to handle mode selection, the predictive current controller isemployed for the inductor current control. The control laws governing each op-erating mode is derived out for valley current control. By making the inductorcurrent in the upcoming switching cycle equivalent to the reference, the duty cycleis predicted. Simulation and experimental results show improvements in currentripple minimization, faster dynamic performance and comparable to traditionalcontrol method.